Performance of a green wall in treating organics, nutrients and pathogens in greywater in a cool climate - Mashreki Sami; Annelie Hedström; Elisabeth Kvarnström; David T. McCarthy; Heinz Gattringer; Marco Hartl; Inga Herrmann (Journal of Water Process Engineering, 2026)

Toluene photo-oxidation and secondary organic aerosol formation: EUROCHAMP-2020 multi-chamber experiments - Petro Uruci; Kalliopi Florou; Marco Paglione; Christos Kaltsonoudis; Bénédicte Picquet-Varrault; Jean-François Doussin; Mathieu Cazaunau; Ari Leskinen; Liqing Hao; Annele Virtanen; David M. Bell; Anke Mutzel; et al. (Journal of Atmospheric Chemistry, 2025)

Assessing trawls size selectivity in Antarctic krill: The role of sex and maturity stages - Ludvig Ahm Krag; Jure Brčić; Bent Herrmann; Marco Nalon; Bjørn Arne Krafft (Regional Studies in Marine Science, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

An ectomycorrhizal fungus alters developmental progression during endogenous rhythmic growth in pedunculate oak - Felix Zimmermann; Marie-Lara Bouffaud; Sylvie Herrmann; Marco Göttig; René Graf; Mika Tarkka; Lars Opgenoorth; Daniel Croll; Martina Peter; Benjamin Dauphin (Mycorrhiza, 2025)
Pedunculate oak ( Quercus robur L.), a long-lived forest tree species, forms symbiotic relationships with ectomycorrhizal (ECM) fungi, which can promote nutrient uptake, stress resilience, and growth. Like other tropical and temperate tree species, pedunculate oak exhibits endogenous rhythmic growth (ERG), a trait conferring the ability to repeatedly alternate root and shoot flushes as well as growth cessation as response to changing environmental conditions. However, the effects of different ECM fungal species on the ERG dynamics remain largely unknown. Here, we investigated the impact of two ECM fungi— Piloderma croceum , a basidiomycete previously shown to promote growth while not found in natural oak stands, and Cenococcum geophilum , an oak-native ascomycete with broad ecological range—on growth performance, biomass partitioning, and ERG patterns in a clonal oak system (clone DF159). By combining in vitro experiments with Bayesian modelling, we show that P. croceum promotes tree growth among treatments, without disrupting the endogenous growth rhythm. In contrast, C. geophilum , while showing high mycorrhization rates, led to reduced biomass accumulation and altered developmental progression through the ERG stages, especially by prolonging the steady state development stage—part of the root flush and characterized by peak net carbon assimilation. Co-inoculation revealed a competitive advantage of C. geophilum in root colonization, yet growth responses resembled those of the control. Our findings demonstrate that ECM species exert species-specific effects on biomass production and temporal development of plants, underscoring the functional importance of ECM fungi in shaping host development. Assessing these interactions provides new insights into the functional diversity of ectomycorrhizal symbiosis and can inform forest management strategies aimed at enhanced resilience in oak-dominated ecosystems under rapidly changing climatic conditions.

A heuristic approach to attenuation of non-relevant metabolites in groundwater and drinking water in Germany - Robin Sur; Marco Herrmann; Namjil Ganbaatar; Alexander Singer (Journal of Consumer Protection and Food Safety, 2024)
A simple and effective heuristic approach was developed and validated to predict the concentration of non-relevant metabolites (nrM) of pesticides in groundwater and drinking water resources based on the simulated concentrations in leachate as used in product authorizations. The evaluation of extensive monitoring data for 50 nrM has demonstrated that the heuristic has a high predictive performance, i.e., concentrations of < 10 µg/l in shallow leachate in the unsaturated zone of the soil in 1 m depth are protective of 1 µg/l in groundwater and raw water in 98 % of cases (49/50 nrM). The reason for the excellent predictive power of the heuristic approach is the large concentration attenuation from leachate to groundwater and to raw water, which was determined to be, on average, 25- and 45-fold, respectively.

Spatial modeling of fire in the atlantic forest considering future climate change scenarios in Rio Grande do Sul state – Brazil - Pamela Boelter Herrmann; Victor Fernandez Nascimento; Fernanda Casagrande; Marcos Wellausen Dias de Freitas; Augusta Carla Klug (Journal of South American Earth Sciences, 2023)

Evaluating the Safety of Intra-Articular Mitotherapy in the Equine Model: A Potential Novel Treatment for Osteoarthritis - Jennifer M. Cassano; Krzysztof Marycz; Marta Horna; Marcos Perez Nogues; Jessica M. Morgan; Daniel B. Herrmann; Larry D. Galuppo; Natalia Vapniarsky (Journal of Equine Veterinary Science, 2023)

Agriculture intensity and landscape configuration influence the spatial use of wildcats across Europe - Héctor Ruiz-Villar; Matteo Luca Bastianelli; Marco Heurich; Stefano Anile; Francisco Díaz-Ruiz; Pablo Ferreras; Malte Götz; Mathias Herrmann; Saskia Jerosch; Fernando Jubete; José María López-Martín; Pedro Monterroso; et al. (Biological Conservation, 2023)

Economic potential of site-specific pesticide application scenarios with direct injection and automatic application assistant in northern Germany - Sandra Rajmis; Isabella Karpinski; Jan-Philip Pohl; Marco Herrmann; Hella Kehlenbeck (Precision Agriculture, 2022)
A growing and promising sector of precision agriculture is the site-specific application of pesticides, having a high potential for reductions in pesticide use. Within the research project ‘AssSys’, site-specific pesticide applications with a direct injection sprayer system and an automatic application assistant were evaluated economically with respect to herbicide and fungicide applications. The application assistant aims to support farmers in decision-making and implementation of site-specific pesticide applications either in the planning stage or as ex-post analysis. The economic assessment was based on field trials and scenario analysis referring to a model farm. The field trials were conducted in 2018 and 2019 in northern Germany. In the scenario analysis, two site-specific application scenarios were compared to conventional uniform treatment (100% of the field area). Weed monitoring was conducted as (1) standard procedure according to integrated pest management, (2) camera-based and (3) drone-based in the field trials. The pesticide application costs include pesticide costs, labour and machine costs of monitoring and pesticide applications. Investment costs of the necessary technical equipment for site-specific applications were included as annual labour and machine costs. As a major key performance indicator of partial budgeting at field level, extended gross margins were calculated. The economic scenario analysis showed pesticide application cost savings from 26 to 66% for site-specific applications compared to conventional applications. The average extended gross margin for site-specific applications of 787 € ha −1 compared to 631 € ha −1 for conventional application showed a clear economic advantage of the site-specific application scenarios. Site-specific pesticide applications can support farmers in implementing precise, sustainable and economically beneficial pesticide management. The technology presented may contribute to meet the goals of the European Green Deal to reduce use and risks of pesticides.

Sea Ice Microbiota in the Antarctic Peninsula Modulates Cloud-Relevant Sea Spray Aerosol Production - Manuel Dall’Osto; Dolors Vaqué; Ana Sotomayor-Garcia; Miguel Cabrera-Brufau; Marta Estrada; Teresa Buchaca; Montserrat Soler; Sdena Nunes; Sebastian Zeppenfeld; Manuela van Pinxteren; Hartmut Herrmann; Heike Wex; et al. (Frontiers in Marine Science, 2022)
Sea spray aerosol (SSA) formation plays a major role in the climate system. The Antarctic Peninsula (AP) is affected by the greatest warming occurring in the Southern Ocean; changes in cryospheric and biological processes are being observed. Whilst there is some evidence that organic material produced by ice algae and/or phytoplankton in the high Arctic contributes to SSA, less is known about Antarctic Sea ice (sympagic) regions. To gain insight into the influence of Antarctic Sea ice biology and biogeochemistry on atmospheric aerosol, we report simultaneous water-air measurements made by means of in situ aerosol chamber experiments. For the first time, we present a methodology showing that the controlled plunging jet aerosol chamber settings do not cause major cell disruption on the studied sea ice ecosystems. Larger sea ice phytoplankton cells (>20 µm; mainly diatoms) tend to sediment at the bottom of the chamber (during the 24h experiment) and likely have a minor role on SSA production. When comparing four chamber experiments - we find that the two producing more SSA are the ones with highest abundance of nanophytoplankton cells (<20 µm; mainly nanoflagellates) as well as viruses. Our marine biogeochemical data show two broad groups of dissolved organic carbon: one rich in carbohydrates and proteic material and one rich in humic-like substances; the latter enhancing SSA production. This work provides unique insights into sea ice productivity that modulates SSA production, with potentially significant climate impacts. Further studies of these types are advised in order to see how microbiology impacts the biogeochemical cycling of elements and how aerosols are formed and processed in cold regions.

Estimating selectivity of experimental diamond (T0) and turned mesh (T90) codends in multi-species Mediterranean bottom trawl - ANDREA PETETTA; BENT HERRMANN; MASSIMO VIRGILI; ROCCO De MARCO; GIOVANNI CANDUCI; DANIEL Li VELI; GIADA BARGIONE; CLAUDIO VASAPOLLO; ALESSANDRO LUCCHETTI (Mediterranean Marine Science, 2020)
The effect of shifting from a diamond mesh codend (T0) to a 90° turned mesh codend (T90) on the size selectivity of seven commercially important species in the Mediterranean bottom trawl fishery was evaluated. During sea trials conducted in the north-western Adriatic, two experimental codends made of 54 mm nominal mesh size netting that differed only in mesh configuration were alternately mounted on the same trawl. Overall, the size selectivity was significantly improved for all the species analysed, shifting from T0 to T90. The difference in the average expected L50values between T90 and T0 was particularly marked in European hake (Merluccius merluccius, 21.26 vs 11.26 cm total length), common squid (Loligo vulgaris, 12.06 vs 7.88 cm mantle length) and mantis shrimp (Squilla mantis, 20.78 vs 13.35 mm carapace length). Both codends had an excessive size selectivity especially for red mullet (Mullus barbatus), Mediterranean horse mackerel (Trachurus mediterraneus) and whiting (Merlangius merlangus), thus involving a commercial loss. These findings demonstrate the efficiency of the T90 codend tested at excluding undersized specimens, especially of hake, whose average L50was above the minimum conservation reference size of 20 cm. The adoption of this practical and inexpensive solution could help improve the management of the demersal resources targeted by the Mediterranean bottom trawl fishery.

Peripheral Alterations in Cytokine and Chemokine Levels After Antidepressant Drug Treatment for Major Depressive Disorder: Systematic Review and Meta-Analysis - Cristiano A. Köhler; Thiago H. Freitas; Brendon Stubbs; Michael Maes; Marco Solmi; Nicola Veronese; Nayanna Q. de Andrade; Gerwyn Morris; Brisa S. Fernandes; André R. Brunoni; Nathan Herrmann; Charles L. Raison; et al. (Molecular Neurobiology, 2017)

Intertemporal choice behavior is constrained by brain structure in healthy participants and pathological gamblers - Bahram Mohammadi; Anke Hammer; Stephan F. Miedl; Daniel Wiswede; Josep Marco-Pallarés; Manfred Herrmann; Thomas F. Münte (Brain Structure and Function, 2016)

The neural basis of impulsive discounting in pathological gamblers - Stephan F. Miedl; Daniel Wiswede; Josep Marco-Pallarés; Zheng Ye; Thorsten Fehr; Manfred Herrmann; Thomas F. Münte (Brain Imaging and Behavior, 2015)

Mediterranean Sea response to climate change in an ensemble of twenty first century scenarios - Fanny Adloff; Samuel Somot; Florence Sevault; Gabriel Jordà; Roland Aznar; Michel Déqué; Marine Herrmann; Marta Marcos; Clotilde Dubois; Elena Padorno; Enrique Alvarez-Fanjul; Damià Gomis (Climate Dynamics, 2015)